Sifat Fisis dan Mekanis Sepuluh Provenans Kayu Mangium (Acacia mangium Willd.) dari Parung Panjang, Jawa Barat Physical and Mechanical Properties of Ten Mangium Wood (Acacia mangium Willd.) Provenances from Parung Panjang, West Java - Nurwati Hadjib; Yusuf Sudo Hadi; Dian Setyaningsih (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
Physical and mechanical properties of ten Mangium provenances have been studied in Forest Products Research and Development Center Bogor.  The 14 years old Mangium was from Parung Panjang, Bogor, West Java, and the provenances were Kiriwo/Scrisa WP-PNG, Wipin District-PNG, Kini WP-PNG, Claudia River-Qld, Lake Muray-PNG, Mata Area WP-PNG, Bimadebun Village WP-PNG, Bilimo District-PNG, Kuru-PNG and Arufi Village-PNG.  Test methods were referring to ASTM D.143-94 (ASTM 2002) for Methods of Testing Small Clear Specimen of Timber.  The results showed that the highest density was Bimadebun Village WP-PNG (0.559 g/cm3) and the lowest was Kiriwo/Serisa WP-PNG (0.493 g/cm3), the highest MOE was Bimadebun Village WP-PNG (101,297 kg/cm2) and the lowest was Wipin District-NG (79,211 kg/cm2), the highest MOR was Bimadebun Village WP-PNG (708.5 kg/cm2) and the lowest was Kini WP-PNG (596.2 kg/cm2), the highest compression strength parallel to grain was Bimadebun Village WP-PNG (421.9 kg/cm2) and the lowest was Wipin District-PNG (342.1 kg/cm2), the highest shearing strength parallel to grain at radial was Arufi Village-PNG (66.2 kg/cm2) and the lowest was Claudia River-QLD (56.4 kg/cm2), the highest shearing strength parallel to grain at tangential was Kuru-PNG (74.4 kg/cm2) and the lowest was Lake Muray-PNG (48.3 kg/cm2).  Based on values of its density, compression strength parallel to grain, shearing strength parallel to grain, the best Mangium provenance from Parung Panjang can be ordered as follow (1) Bimadebun Village WP-PNG, (2) Kuru-PNG, (3) Mata Area-PNG, (4) Arufi Village-PNG, (5) Bilimo District-PNG, (6) Kini WP-PNG, (7) Wipin District-PNG, (8) Kiriwo Serisa-PNG, (9) Claudia River-QLD and (10) Lake Muray-PNG.